Luteolin Ameliorates Experimental Pulmonary Arterial Hypertension via Suppressing Hippo-YAP/PI3K/AKT Signaling Pathway - Zuo, Wanyun; Liu, Na; Zeng, Yunhong; Xiao, Zhenghui; Wu, Keke; Yang, Fan; Li, Biao; Song, Qingqing; Xiao, Yunbin; Liu, Qiming (Frontiers in Pharmacology, 2021)
Luteolin is a flavonoid compound with a variety of pharmacological effects. In this study, we explored the effects of luteolin improving monocrotaline (MCT) induced rat pulmonary arterial hypertension (PAH) and underlying mechanisms. We constructed a rat PAH model through MCT injection. In this model, luteolin improved pulmonary vascular remodeling and right ventricular hypertrophy, meanwhile, luteolin could inhibit the proliferation and migration of pulmonary artery smooth muscle cells induced by platelet-derived growth factor-BB (PDGF-BB) in a dose-dependent manner. Moreover, our results showed that luteolin could downregulate the expression of LATS1 and YAP, decrease YAP nuclear localization, reduce the expression of PI3K, and thereby restrain the phosphorylation of AKT induced by PDGF-BB. In conclusion, luteolin exerts protective effects against experimental PAH, which are partly mediated through suppressing HIPPO-YAP/PI3K/AKT signaling pathway. Therefore, luteolin might become a promising candidate target medicine for PAH.